2022
DOI: 10.2196/33972
|View full text |Cite
|
Sign up to set email alerts
|

Features and Components Preferred by Adolescents in Smartphone Apps for the Promotion of Physical Activity: Focus Group Study

Abstract: Background There is solid evidence that lack of physical activity (PA) is a risk factor for chronic diseases. Sufficient levels of PA in childhood and adolescence are particularly important, as they can set the standards for PA levels in adulthood. The latest reports show that only a small percentage of adolescents reach the recommended levels of PA in European Union countries at the age of 15 years. In view of the scale of the problem, it is crucial to develop interventions that promote and suppor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In addition, these 2 studies revealed that users are more interested in fun, easy-to-use, and functional apps that offer visual appeal, as highlighted in a previous study by Schoeppe et al [ 45 ]. Considering that the target participants are children and adolescents, fun and user-friendly apps will assist in the PA monitoring of this specific age group [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these 2 studies revealed that users are more interested in fun, easy-to-use, and functional apps that offer visual appeal, as highlighted in a previous study by Schoeppe et al [ 45 ]. Considering that the target participants are children and adolescents, fun and user-friendly apps will assist in the PA monitoring of this specific age group [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the target participants are children and adolescents, fun and user-friendly apps will assist in the PA monitoring of this specific age group [46].…”
Section: Pros and Cons Of Each Appmentioning
confidence: 99%
“…The advertisement with study details was disseminated via the school’s email service, seeking to attract adolescents who were insufficiently active yet, on principle, willing to increase their PA participation. In addition, several adolescent students of local Luxembourgish schools were recruited from the participant list of the focus group discussion, which took place earlier and has been described elsewhere [ 76 ]. The advertisement contained general information about the study and informed potential participants that they would be remunerated for taking part.…”
Section: Methodsmentioning
confidence: 99%
“…BCTs can be applied in multiple contexts, such as integration into apps to promote PA (Brannon & Cushing, 2015). Goal setting, planning, feedback, reward, self-observation, social comparison, and social support are BCTs that children and adolescents have identified as interesting, attractive, and motivating (Baumann et al, 2022;Daryabeygi-Khotbehsara et al, 2021;Domin et al, 2022;Schoeppe et al, 2017). Schoeppe et al (2017) examined the effect of BCT on app quality and observed that the number of BCTs correlates positively with app quality.…”
Section: Introductionmentioning
confidence: 99%